Layanan Informasi melalui Voluntary Counseling and Testing pada Kelompok Resiko Tinggi (Analisis Bimbingan Konseling Islam) - Fiana, Anis Lud; Ismail, Amrizarois; Maullasari, Sri; Rohman, Isa Aulia (IAIN Kudus, 2021)
Information Services through Voluntary Counseling and Testingfor High-Risk Groups (Islamic Counseling Guidance Analysis). Information services allow clients to receive and understand various information in various fields such as education, social, health, and others. The counseling program in the information service Voluntary Counseling and Testing (VCT) aims to provide knowledge about maintaining health to reduce the spread of HIV/AIDS. Anyone can experience cases of contracting the HIV/AIDS virus, one of which is the high-risk group for sex men (MSM), transgender (TG), and people who inject drugs (PWID). This study aims to provide an analysis of the implementation of information services through VCT in the prevention of HIV/AIDS transmission in high-risk groups. The design of this study used a descriptive qualitative method by taking samples from assisted groups in PKBI Semarang City. Information services in VCT contain the knowledge of HIV/AIDS transmission and prevention. This study shows the effectiveness of information services provided by officers in the VCT process in preventing transmission of HIV/AIDS in the high-risk group to be analyzed using the Islamic counseling guidance model.Keywords: Information Services, Voluntary Counseling, and Testing, HIV AIDS, High-Risk Groups